Faktor-Faktor Yang Mempengaruhi Praktik Perataan Laba (Income Smoothing) Studi empiris pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia (BEI) tahun 2011-2014 - Styaningrum, Nina, Drs. Yuli Tri Cahyono , M.M., Akt., CA (2016)
The purpose of this research is to examine the influence of company size, financial leverage, net profit margin, operatig profit margin, return on assets, and company's development toward the practice of income smoothing. The sample used in this study at 39 manufacturing companies listed on the Indonesian Stock Exchange beginning in 2011 to 2014 were obtained by purposive sampling method. Independent variable that examined in this research are company size, financial leverage, net profit margin, operating profit margin, return on assets, and company's development. Eckel index was used to determine firms who did income smoothing and didn't do income smoothing. The hypothesis was examined using binary logistic regression. According to hypothesis test, the result of this research is company size have negative and significant influence toward the practice of income smoothing. Financial leverage which proxied by DER (dept to total equity) have positive and significant influence toward the practice of income smoothing. ROA (return on assets) and net profit margin have not significant influence toward the practice of income smoothing. company's development which proxid by EPS (earning per share)and operating profit margin and have not significant influence toward the practice of income smoothing.